EUPHEMICTIC EXPRESSION IN THE REPORTING OF SEXUAL HARASSEMENT ON THE INSTAGRAM ACCOUNT ‘INSIDE LOMBOK’ - Yuni Selviani Yuni Selviani; Moh Gufron Moh Gufron; Muh. Junaidi Muh. Junaidi (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2026)
This research analyzes the types and social functions of euphemistic expressions used in the reporting of sexual harassment cases on the ‘Inside Lombok’ Instagram account. This research uses a qualitative descriptive method with a discourse analysis approach. Data were obtained from captions and Instagram posts related to sexual harassment cases. The research results show that there are eight types of euphemisms used, namely substitution, orthographic variation, circumlocution, generalization, technical terms, abbreviation, metaphor, and understatement. Among all these types, circumlocution is the most dominant, indicating a tendency for the media to use indirect expressions in conveying sensitive information. Additionally, this study found four main social functions of euphemisms, namely namely identity protection, censorship evasion and conformity with digital platforms, discourse neutralization and prevention of collective stigmatization, and interpretation management and public perception building. This study concludes that euphemisms in digital media reporting not only function as a strategy of linguistic politeness but also as a discursive tool that influences public representation and understanding of the issue of sexual harassment on social media.